A Method For Estimating Rfid Protocol Execution Time Based On Flowgraph Model - Tan, Aik Theng (2021)
The TPG protocol designed to efficiently group all tags according to a given partition so that tags in the same group will have the same group ID. Using the TPG protocol; the RFID reader sends the group ID followed by the IDs of the RFID tags only once without repeatedly sending the same group ID to each RFID tag. An existing theoretical solution proposed to measure the execution time of the TPG protocol does not provide comprehensive solutions. For example, the missing solutions consider the RFID tag response time and can only be used to measure the TPG protocol execution time in the RFID reader-to-RFID tag (one-to-many) environment, but not in the RFID reader-to-RFID tag (many-to-many) environment. A flowgraph model is proposed in this research to overcome the limitations of the existing TPG protocol equation. It is essential to measure the execution time of the TPG protocol in a many-to-many RFID network topology because the application of the TPG protocol is not limited to a one-to-many RFID network topology. Currently, the many-to-many RFID network topology widely uses to improve authentication efficiency. Therefore, measuring the execution time of the TPG protocol in a many-to-many RFID network topology is essential to determine the efficiency of the TPG protocol. The proposed equations based on the flowgraph model to estimate the total execution time of the TPG protocol can apply in three types of RFID network topologies: one-to-one (RFID reader and RFID tag), one-to-many (RFID reader and RFID tags), and many-to-many (RFID reader and RFID tags).